Comparing the Frequency of Migraine Headaches in Children With and Without Enuresis: Migraine Headache in Enuresis - Pourhossein Miri, Hossein; Shariatmadari, Fakhreddin; Kahbazi, Manijeh; Yousefichaijan, Parsa; Javaheri, Javad (Journal of Pediatric Nephrology, 2025)
Background and Aim: Nocturnal enuresis and migraine are common disorders among children, each having a major impact on the health and life status of the children and their families. In several children, these two disorders have also been observed together. Accordingly, this study evaluates the relationship between migraine and nocturnal enuresis by examining the frequency of migraine in children with nocturnal enuresis. Methods: In this analytical cross-sectional study, the experimental group includes children with nocturnal enuresis, who were diagnosed by a pediatric nephrologist. The control group is comprised of children without nocturnal enuresis. In both groups, the frequency of migraine headaches diagnosed by pediatric neurologists was checked and finally, the frequency obtained in the two groups was compared. The sample size was 47 people for each group. Information analysis was done through analytical statistics, including tables and statistical charts and their analysis. Independent t-test, the chi-square test, the Fisher test, and if necessary, equations were used to analyze the non-parametric data. Results: The distribution of frequency between gender and nocturnal enuresis was the same in two groups (57.4% male and 42.6% female). Also, the mean age in the patient category was 7.6±2.3 years and in the healthy category was 8.3±2.6 years. The frequency distribution between having migraine, migraine with aura, the number of times experiencing headache, and family history at the time of admission were the same in the two groups. Conclusion: In conclusion the frequency of migraine, migraine with aura, the number of times experiencing headache, and family history of migraine were the same in the two groups